Les représentations des étudiants tuteurs en masso-kinésithérapie sur le dispositif de tutorat entre pairs - Cédric Dabo; Sylvain Connac (Recherches en Éducation)
The peer tutoring is a help device between students that is find in different cursus. This research is focused on the physiotherapist’s peer tutoring. It is a voluntary based program; the goal of this study is to better understand what the tutoring’s representation of the physiotherapist’s student tutor are. To answer this research question, I use a methodology of phenomenology approach by triangulation. This one covers the data of three different collections of information: semi structured student tutors interviews, semi structured tutored students interviews, and cover letters written by student tutors who were candidate of the tutoring. The results of this research allow us to see that the physiotherapist student tutors consider the peer tutoring like a program with multiple functions: help device, teaching device, revision device, privileged relation device, and exchange of service de-vice. These representations lead to distinguish peer tutoring from other assistance or support devices: monitoring, mentoring, companionship and sponsorship. This study of tutoring allows to emphasize its essential characteristics and primary educational intentions.